Study on Biomedical activity of stem and leaf extraction of Heliotropium marifolium (J. Kocnig ex Retz.) (Advances in Applied Biological Research, 2025)
New anti-diabetic compounds can be obtained from Indian herbal remedies,  which are employed in the ancient Ayurvedic approach to manage hyperglycemia.  A common medicinal plant, H. marifolium is a significant reservoir of compounds  with potent antioxidant action. The main objective of the study was to find out  the anti-inflammatory activities, antioxidant and antidiabetic effect of selected  medicinal plant. Conventional parameters such as DPPH, ABTS, hydroxyl,  superoxide radical, nitric oxide, and hydrogenperoxide assay were performed. The  chromogenic iodine technique was used to quantitatively determine the activity  of extracts in relation to amylase inactivation. At 250µg, the leaves extraction  had a much stronger scavenge action (>75%) than the stem extraction (
Keywords: Amylase; Hyperglycemia; Herbal medicine; Inflammation; DPPH